SGLT2 inhibitors in patients with cirrhosis and diabetes mellitus: A tertiary center cohort study and insights about a potential therapeutic target for portal hypertension. Issue 3 (6th December 2020) - Saffo, Saad; Garcia‐Tsao, Guadalupe; Taddei, Tamar
Abstract : Highlights Sodium glucose cotransporter 2 (SGLT2) inhibitors have favorable pleiotropic effects in patients with diabetes mellitus and cardiovascular or renal disease. The benefits of SGLT2 inhibitors may extend to portal hypertension, but they have not been formally evaluated in patients with cirrhosis. Our study is the first to provide clinical data for SGLT2 inhibitors in a cohort of patients with cirrhosis, and our findings support ongoing evaluation in the form of a clinical trial.